2016
DOI: 10.1111/jep.12612
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes after surgical resection for colorectal cancer in South Australia

Abstract: Short-term outcomes following CRC surgery may be improved through strategies to increase earlier detection and reduce emergency admissions. Socioeconomic and regional disparities require further examination of health system factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…The overall elective resection rate of 81.5% and emergency resection rate of 18.5% was comparable to previous Australian studies, which estimated that the elective CRC resection rate was 83–93% . Our study showed that low volume hospitals performed a higher proportion of emergency resections, between 25% and 32%.…”
Section: Discussionsupporting
confidence: 84%
“…The overall elective resection rate of 81.5% and emergency resection rate of 18.5% was comparable to previous Australian studies, which estimated that the elective CRC resection rate was 83–93% . Our study showed that low volume hospitals performed a higher proportion of emergency resections, between 25% and 32%.…”
Section: Discussionsupporting
confidence: 84%
“…This review therefore included 59 articles published between 1993 and 2016, reporting on a total of 2 698 403 patients ( Table S2, supporting information). These studies included data collected between 1976 and 2014 from eight countries.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially pertinent in the presence of a high prevalence of postoperative complications. Previous research in Australia found that patients from higher socio-economic areas had a lower risk of developing postoperative complications ( Beckmann et al , 2016 ), reinforcing the need for adequate postoperative care facilities in the most deprived areas. Comparing postoperative care resourcing between institutions in more and lesser deprived areas could provide some explanation behind socio-economic differences in 90-day colon cancer mortality and should be examined in more detail.…”
Section: Discussionmentioning
confidence: 96%